Prooxidant properties of camu camu (Myrciaria dubia) - Guija, Henry (2005)
Objective: To determine the effect of ferric ion on the prooxidant properties of camu camu (Myrciaria dubia). Design: Analytic, experimental, prospective, and longitudinal study. Materials and Methods: Camu camu (Myrciaria dubia) is a fruit characterized for its high vitamin C content. The prooxidant properties of camu camu by the effect of Fe(III), EDTA, thiourea and mannitol was determined. Results: A mixture of camu camu and Fe-III in phosphate buffer at pH 7,4 notoriously increased the generation of free radicals by kinetic saturation mechanism. This effect depended on metal concentration. The presence of thiourea or mannitol, components with known antioxidant action, inhibited free radicals generation, while EDTA increased free radical formation. Conclusion: Camu camu increases free radicals generation in the presence of Fe(III) and EDTA.